Altenatif Strategi pada UMKM Kopi menggunakan Analisis SWOT - M. Adi Trisna Wahyudi; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardana (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
Coffee organizations at the international level report that world coffee consumption continues to increase every years. This growth in world coffee consumption has had a positive impact on coffee MSMEs in Indonesia, including Langgano Jombang and Kikopi Surabaya. The problem faced by coffee MSMEs such as Langgano Jombang and Kikopi Surabaya is that they are unable to compete with competitors. This research was carried out using a qualitative case study approach. With stages, first, identifying internal factors and external factors for MSMEs in marketing products and then determining alternative strategies. And the research results found that a strategy to increase the Langgano Jombang and Kikopi Surabaya markets that can be done is to use power as a tool to seize opportunities. Or in the Strengths – Opportunities quadrant.